Political dimensions of social-ecological transformations: polity, politics, policy - Melanie Pichler (Sustainability: Science, Practice, & Policy, 2023)
AbstractSocial-ecological transformations are necessarily political. That is, they are shaped by intentional interventions to steer societies and its metabolism but also by conflicts and power relations over the very strategies to do so. In borrowing from different strands in transition and transformation research, this article systematizes the political dimensions of social-ecological transformations along the lines of polity, politics, and policy. It thus combines the analysis of economic and institutional structures (polity) with a focus on conflicts and power relations (politics) that influence and shape concrete proposals for transformative change (policy). First, with regard to the polity, the article shows that the interplay of capitalism and fossil energy has created institutional structures (e.g., the modern state and liberal consumer democracies) that often constrain—rather than naturally support—transformative change. These structures shape transformation processes in that they prioritize certain political strategies over others and channel policies toward incremental change. Second, in terms of the politics, the article develops a conflict-oriented perspective that helps to better understand the power-laden process of social-ecological transformations. Finally, with respect to the policies, the article discusses characteristics of policies that are able to challenge economic and institutional structures to open up opportunities for transformative change.